2009
DOI: 10.1111/j.1471-4159.2009.06000.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐amnesic properties of (±)‐PPCC, a novel sigma receptor ligand, on cognitive dysfunction induced by selective cholinergic lesion in rats

Abstract: J. Neurochem. (2009) 109, 744–754. Abstract Previous studies have reported that selective sigma‐1 agonists may improve cognitive abilities in experimental animals possibly via a cholinergic mechanism. However, the issue of a direct action on to sigma‐1 receptors in memory‐related brain areas has been much less investigated. The newly synthetised compound methyl(1R,2S/1S,2R)‐2‐[4‐hydroxy‐4‐phenylpiperidin‐1‐yl)methyl]‐1‐(4‐methylphenyl) cyclopropanecarboxylate [(±)‐PPCC] has recently been shown to possess high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 60 publications
2
45
0
Order By: Relevance
“…Antonini et al (2009; demonstrated that occupation of the rat σ1 receptor by PPCC and (-)-MR22 can prevent cognitive impairment caused by the combined administration of the muscarinic receptor antagonist atropine and immunotoxin 192 IgG-saporin, which leads to a loss of cholinergic neurons in the basal forebrain. Those authors suggest that the observed PPCC and (-)-MR22 mediated neuroprotection might be due to stabilization of IP3 receptors that prolong the flow of calcium into the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antonini et al (2009; demonstrated that occupation of the rat σ1 receptor by PPCC and (-)-MR22 can prevent cognitive impairment caused by the combined administration of the muscarinic receptor antagonist atropine and immunotoxin 192 IgG-saporin, which leads to a loss of cholinergic neurons in the basal forebrain. Those authors suggest that the observed PPCC and (-)-MR22 mediated neuroprotection might be due to stabilization of IP3 receptors that prolong the flow of calcium into the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of the competitive cholinergic muscarinic receptor antagonist scopolamine causes cognitive dysfunctions similar to those observed in normal aging and AD (Ebert and Kirch, 1998;Bejar et al, 1999;Klinkenberg and Blokland, 2010). A scopolamine-dependent model of cognitive deficits has been used to screen for potential cognition-enhancing drugs (Flood and Cherkin, 1986;Ennaceur and Meliani, 1992;Antonini et al, 2009;Klinkenberg and Blokland, 2010). Since the sigma σ1 receptor is known to potently modulate cholinergic neurotransmission at different levels (van Waarde et al, 2011), we investigated the effect of our novel σ1 receptorselective ligand, LS-1-137, on scopolamine-dependent cognitive deficits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…a total absence of cholinergic neurons in the basal forebrain nuclei [2]. Pretreatment of animals with the sigma-1 receptor antagonist BD1047 blocked the anti-amnesic effects of (±)-PPCC [2].…”
Section: Acetylcholine and Sigma-1 Receptor Functionmentioning
confidence: 99%
“…In a recent investigation, we have reported that the compound (±)-PPCC, a highly selective sigma-1 receptor agonist, with virtually no affinity for cholinergic receptors, effectively ameliorates spatial learning and memory performance in rat paradigms of mild or severe cognitive dysfunction via a direct interaction with sigma-1 receptors [35].…”
Section: Introductionmentioning
confidence: 99%